Real-Time Connected Car Services - Yogarayan, S.; Azman, A.; Abdul Razak, S.F.; Raman, K.J.; Abdullah, M.F.A.; Ibrahim, S.Z.; Muhamad Amin, A.H.; Sonai Muthu, K. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
In recent years, the patterns of connected car are tied in with giving drivers more answers for making the journey consistent. Vehicles today are outfitted with high innovation highlights and in-vehicle availability. The Integrated Connected Vehicle Services is produced to convey an incorporated driving experience to all vehicle owners, to make a communication stage for drivers to impart and share data between vehicles. The system allows to discover nearby vehicles inside range, giving the driver early notice caution of crisis vehicles inside certain range. Moreover, the system likewise enables the driver to share basic data which later plots into the maps for alternate drivers to view and plan the journey. The information of transmission between the vehicles are incorporated through firebase cloud services. Firebase is known as an effective cloud database and ready to screen the application development.